1996
DOI: 10.1021/ma950688d
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Synthesis of Narrow Molecular Weight Distribution Water-Soluble Poly(N,N-dimethylacrylamide) and Poly(N-acryloyl-N ‘-methylpiperazine)

Abstract: Water-soluble poly(N,N-dimethylacrylamide) (PDMA) and poly(N-acryloyl-N ‘-methylpiperazine (PAMP) were prepared in tetrahydrofuran at −78 °C by anionic polymerization in the presence of monofunctional initiators such as (triphenylmethyl)lithium, or -cesium or the difunctional initiators (1,1,4,4-tetraphenylbutyl)lithium, -potassium, or -cesium or cesium naphthalenide. Polymerizations initiated especially in the presence of cesium as counterion proceeded in a homogeneous manner and gave polymers having controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
103
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 33 publications
(45 reference statements)
5
103
0
Order By: Relevance
“…NH O n Poly(N-methylacrylamide) PMAAm [207] Estimated T cp > 100 • C T g = 178.5 • C, M w = 185, 000 g/mol, PDI = 3.6 LCST-type copolymers with styrene, 20 [195,207,222,236,[454][455][456]; LCST: estimated T cp > 100 • C [207,454], T cp ≈ 200 • C [195] Chemically crosslinked hydrogel shrinks upon heating [207] T g = 125.7 • C, M w = 156, 000 g/mol, PDI = 3.4 [207]; [223]; isotactic PDMAAm is highly crystalline and only partially soluble in water [457,458]; however, in [223] PDMAAm samples are reported to be soluble in water regardless of the tacticity LCST type copolymers with styrene, 20 • C < T cp < 100 • C [207] and with 2-methoxyethylacrylate, 9 • C < T cp < 80 • C [454]; AB diblock copolymers [455] (continued) …”
mentioning
confidence: 99%
“…NH O n Poly(N-methylacrylamide) PMAAm [207] Estimated T cp > 100 • C T g = 178.5 • C, M w = 185, 000 g/mol, PDI = 3.6 LCST-type copolymers with styrene, 20 [195,207,222,236,[454][455][456]; LCST: estimated T cp > 100 • C [207,454], T cp ≈ 200 • C [195] Chemically crosslinked hydrogel shrinks upon heating [207] T g = 125.7 • C, M w = 156, 000 g/mol, PDI = 3.4 [207]; [223]; isotactic PDMAAm is highly crystalline and only partially soluble in water [457,458]; however, in [223] PDMAAm samples are reported to be soluble in water regardless of the tacticity LCST type copolymers with styrene, 20 • C < T cp < 100 • C [207] and with 2-methoxyethylacrylate, 9 • C < T cp < 80 • C [454]; AB diblock copolymers [455] (continued) …”
mentioning
confidence: 99%
“…These CRPs are applicable to acrylamide, N-monosubstituted acrylamide, and N,N-disubstituted acrylamide (DAA) except for those bearing radical-sensitive groups, such as N-allyl acrylamide and N-2-thioethyl acrylamide. On the other hand, anionic polymerization is only suitable for DAAs without any anionsensitive groups though applicable DAAs are limited to N,Ndimethylacrylamide (DMAA), [9][10][11] N,N-diethylacrylamide (DEAA), [10][11][12][13] N,N-di-n-propylacrylamide (DnPAA), [11] Nethylmethylacrylamide (EMA), [11] N-acryloylpyrrolidine (APY), [11] N-acryloylpiperidine (API), [11] N-acryloylmorpholine (NAM), [11] N-acryloyl-2-methylaziridine, [14] Nacryloylazetidine, [15] N-methoxymethyl-Nisopropylacrylamide, [16] N-propyl-N-(3-triisopropoxysilylpropyl)acrylamide, [17] and N-propyl-N-(3-triethoxysilylpropyl)acrylamide. [17] Nevertheless, the anionic polymerization of DAA is still the most reliable method for the precise synthesis of the structurally defect-free polyacrylamides because the CRPs inevitably cause side reactions due to radical transfers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in a recent publication Xie and Hogen-Esch reported that fluorenyl caesium cannot polymerize DMAA. [10] In contrast, the salts of the fluorenyl anion (fluorene, pK a = 22.6 [6] ) are known to initiate the polymerization of MMA, [3,6] but not that of nonpolar monomers. [6] These considerations prompted us to examine the possibility of DMAA copolymerization with styrene and butadiene and to perform test experiments that have led to quite unexpected results.…”
Section: Introductionmentioning
confidence: 99%